2021
DOI: 10.12973/eu-jer.10.3.1505
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Meaning of the Equal Sign: A Case Study of Middle School Students in the United Arab Emirates

Abstract: <p style="text-align: justify;">The equal symbol has been used in diverse mathematical frameworks, such as arithmetic, algebra, trigonometry, set theory, and so on. In mathematical terms, the equal sign has been used in fixed command of standings. The study reports on the students meaning and interpretations of the equal sign. The study involved Grade 6, 7, and 8 students in a secondary school in Alain, United Arab Emirates (UAE). Much of the earlier research done on the equal sign has focused on the pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The descriptive approach was used to answer the study questions, and to achieve the objectives, by recognizing the status of teaching mathematics in simultaneous virtual classes in the light of the Covid 19 pandemic (Wardat et al, 2021), specifically uncovering thereby the degree of teaching practices of mathematics teachers in simultaneous virtual classes in the light of the Covid 19 pandemic from the teachers' perspectives by using questionnaires.…”
Section: The Methodologymentioning
confidence: 99%
“…The descriptive approach was used to answer the study questions, and to achieve the objectives, by recognizing the status of teaching mathematics in simultaneous virtual classes in the light of the Covid 19 pandemic (Wardat et al, 2021), specifically uncovering thereby the degree of teaching practices of mathematics teachers in simultaneous virtual classes in the light of the Covid 19 pandemic from the teachers' perspectives by using questionnaires.…”
Section: The Methodologymentioning
confidence: 99%
“…As well as its role in developing students' abilities to justify, prove and solve problems. As well as preparing a conscious and creative generation qualified with knowledge and skills in various fields, teaching mathematics in the third millennium needs to provide a fertile environment with mathematical concepts that the student needs to deal with its successive variables and successive developments (Wardat et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The mind is an active member responsible for providing experiences for students to learn building concepts that constitute continuous learning in mathematics. Whereas (Kusmayanti, I, Sumantri, S. & Noornia, A., 2018) see concept-rich instruction as active processes by which students organize, construct and recreate concepts presented to them in learning experiences time (Stoica & Wardat, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These results are in line with the findings reported by Huang and Huang (2015), who reported that the digital games significantly improved the low-achieving students' motivation and performance in the learning process. The motivation they gained through solving more games with different levels encouraged them to play more games and collect more points (Wardat et al, 2021).…”
Section: Discussionmentioning
confidence: 99%